The Food Crisis in Ethiopia & Egypt: Contrasting Hydrological & Economic Barriers to Development - Stokes, Leah; Scozzaro, A. Tianna; Haller, Jennifer (Consilience, 2010)
Water scarcity is often underemphasized in analyses of the global food crisis. Ethiopia and Egypt are compared in order to understand the differences between physical and economic water scarcity and their impacts on food security. Water availability in Egypt is low compared with Ethiopia; however, irrigation is widely practiced in Egypt, supporting a variety of crops, including water intensive species, and ensuring food security. In Ethiopia, lack of water infrastructure, such as irrigation and catchments and a lack of institutional capacity limit food security. In addition, Ethiopia’s GDP is strongly linked to agricultural exports. As a result, Ethiopia’s economy is tightly coupled with rainfall. The adaptation Egypt has taken to overcome physical water scarcity is in stark contrast with the lack of institutional capacity Ethiopia has to harness its water abundance. The result is chronic food insecurity in Ethiopia, which Egypt has been able to overcome, at least in the short term. Climate change may pose additional stressors for water availability in both countries. Solutions to overcome food insecurity in Ethiopia include irrigation, growing less water intensive crops and improving governance and climate information access.